Heart rate recovery in elite Spanish male athletes - Peinado, A. B.; Benito, P. J.; Barriopedro, M.; Lorenzo, I.; Maffulli, N.; Calderón, F. J. (The Journal of Sports Medicine and Physical Fitness, 2014)
AIM: During postexercise recovery, heart rate (HR) initially falls rapidly, followed by a period of slower decrease, until resting values are reached. The aim of the present work was to examine the differences in the recovery heart rate (RHR) between athletes engaged in static and dynamic sports. METHODS: The study subjects were 294 federated sportsmen competing at the national and international level in sports classified using the criteria of Mitchell et al. as either prevalently static (N.=89) or prevalently dynamic (N.=205). Within the dynamic group, the subjects who practised the most dynamic sports were assigned to further subgroups: triathlon (N.=20), long distance running (N.=58), cycling (N.=28) and swimming (N.=12). All athletes were subjected to a maximum exertion stress test and their HR recorded at 1, 2, 3 and 4 min (RHR1,2,3,4) into the HR recovery period. The following indices of recovery (IR) were then calculated: IR1 = (HRpeak - RHR1,2,3,4) / (HRmax - HRrest) * 100, IR2 = (HRpeak - RHR1,2,3,4)/(HRmax / HRpeak), and IR3 = HRpeak - RHR1,2,3,4. The differences in the RHR and IR for the static and dynamic groups were examined using two way ANOVA. RESULTS: The RHR at minutes 2 (138.7±15.2 vs. 134.8±14.4 beats/min) and 3 (128.5±15.2 vs. 123.3±14.4 beats/min) were significantly higher for the static group (Group S) than the dynamic group (Group D), respectively. Significant differences were seen between Group D and S with respect to IR1 at minutes 1 (26.4±8.7 vs. 24.8±8.4%), 2 (43.8±8.1 vs. 41.5±7.8%), 3 (52.1±8.3 vs. 49.1±8%) and 4 (56.8±8.6 vs. 55.4±7.4%) of recovery. For IR2, significant differences were seen between the same groups at minutes 2 (59.7±12.5 vs. 55.9±10.8 beats/min) and 3 (71.0±13.5 vs. 66.1±11.4 beats7min) of recovery. Finally, for IR3, the only significant difference between Group D and S was recorded at minute 3 of recovery (72.2±12.5 vs. 66.2±11.5 beats·min-1). CONCLUSION: This work provides information on RHR of a large population of elite Spanish athletes, and shows marked differences in the way that HR recovers in dynamic and static sports.